Experimental Study of the Cooling of Electrical Components Using Water Film Evaporation. (4th December 2012) - Harmand, S.; Gil, D. Pérez; Zouitene, S.; Remmerie, L.; Benazzouz, T.; Cardarelli, F.
Abstract : Heat and mass transfer, which occur in the evaporation of a falling film of water, are studied experimentally. This evaporation allows the dissipation of the heat flux produced by twelve resistors, which simulate electrical components on the back side of an aluminium plate. On the front side of the plate, a falling film of water flows by the action of gravity. An inverse heat conduction model, associated with a spatial regularisation, was developed and produces the local heat fluxes on the plate using the measured temperatures. The efficiency of this evaporative process has been studied with respect to several parameters: imposed heat flux, inlet mass flow rate, and geometry. A comparison of the latent and sensible fluxes used to dissipate the imposed heat flux was studied in the case of a plexiglass sheet in front of the falling film at different distances from the aluminium plate.